A comparative study between deep inferior epigastric artery perforator flap breast reconstruction and DIEP flap breast reconstruction coupled with vascularized lymph node transfer: Improving the quality of life of patients with breast cancer related lymphedema without affecting donor site outcomes. Issue 3 (30th May 2022) - Di Taranto, Giuseppe; Coleman, Grant J.; Hardwicke, Joseph; Wallis, Katy L.; Skillman, Joanna
Abstract: Background: Despite simultaneous microvascular breast reconstruction (MBR) and vascularized lymph node transfer (VLNT) gaining wide popularity as a potential treatment for breast cancer related lymphedema (BCRL), there is a lack of evidence supporting the procedure. There are few reports in the literature, and no study has compared simple deep inferior epigastric artery perforator (DIEP) to simultaneous DIEP flap and VLNT. Patients and methods: A retrospective analysis of our series of DIEP flaps was conducted. Patients presenting with BCRL who had delayed MBR and simultaneous VLNT were selected. Thirty‐two patients were included and compared with a control group of delayed MBR with DIEP flap alone. Clinical evaluation, circumference reduction rate, and LYMQOL questionnaire were used to compare preoperative and postoperative findings in the study group. A digital version of BREAST Q questionnaire was administered to all patients. Results: Thirty‐two patients were enrolled in the study group, with a mean follow‐up of 42.5 ± 25.7 months and mean age of 54.1 ± 7.8 years. The mean circumference reduction rate was 46.1 ± 52.3, 39 ± 42.3, 47.5 ± 53.5, 39.2 ± 52.4, 33.6 ± 50.1 at the deltoid insertion, above the elbow, below the elbow, at the mid‐forearm and wrist respectively. Postoperative LYMQOL scores significantly improved (function 1.21, appearance 1.15, symptoms 1.34, mood 1.33, overall QOLscore 8.6) from preoperative baseline ( p  < .001). There was no significant difference in term of outcomes and complications rate of the donor site between the study and control groups. Conclusions: Simultaneous DIEPandVLNT improves the HRQOL of patients with lymphedema. Coupling VLNT with abdominal flap does not increase the morbidity of donor site.